Critical issues in electronic media - Penny, Simon (Albany : State University of New York Press, 1995)
Critical Issues in Electronic Media is an interdisciplinary sourcebook that offers new critical perspectives directly related to, or arising from, the practice of electronic media art. It sketches the changing topology of culture as it enters electronic space and specifically addresses questions of art practice in that space. Some of the contributions focus on the dynamics of specific emerging media such as interactive media, while others look at the cultural conditions formed by, and forming around, new technological complexes. Still others examine contemporary technocultural manifestations against a background of social and technological history. The contributors are professionally and geographically diverse, representing professional fields such as computer graphics, video, sound, drama, and visual arts as well as media, cultural and literary theory, and the social sciences. Together, these essays provide a rich survey of contemporary technological critique and offer a perspective on creative practice in technological media.
Suck on this, planet of noise! / McKenzie Wark -- In/quest of presence : virtuality, aurality, and television's Gulf War / Frances Dyson -- Consumer culture and the technological imperative : the artist in dataspace / Simon Penny -- Technology is the people's friend : computers, class, and the new cultural politics / Richard Wright -- Utopian plagiarism, hypertextuality, and electronic cultural production / Critical Art Ensemble -- Virtual worlds : fascination and reactions / Florian Rötzer -- Transforming mirrors : subjectivity and control in interactive media / David Rokeby -- Encapsulated bodies in motion : simulators and the quest for total immersion / Erkki Huhtamo -- Image, language, and belief in synthesis / George Legrady -- Track organology / Douglas Kahn -- On monitors and men and other unsolved feminine mysteries : video technology and the feminine / Nell Tenhaaf -- The irresistible interface : video's unknown forces and fire-lit waves / David Tafler -- One video theory (some assembly required) / Gregory Ulmer.
Includes bibliographical references (pages 275-285) and index.
Print version record.
JSTOR
Keywords: Video art; Computer art; Interactive multimedia; Art vidéo.; Art par ordinateur; Multimédias interactifs; video art; computer art (visual works); ART -- Popular Culture; Computer art; Interactive multimedia; Video art; Mediakunst; Computerkunst